Predicting TV in the year 2013 - Zheng, H.; Aalto, T.; Kivelä, J.; Lugmayr, Artur; Bäckman, E.; Hartimaine, J.; Niskanen, S.; Manninen, T.; Rapeli, J. (2011)
TV technology is rapidly advancing. This paper focuses on describing the current trends of television industry, and predicting the situation until 2013. Now it seems that the fusion among TV, Internet and personal mobile device is unstoppable depending on the current trends. As interactive TV, HDTV, 3DTV and all of these television devices which could enhance consumer experience and interactive activities have gradually become the mainstream. © 2011 ACM.